2023
DOI: 10.1159/000529279
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Anticancer Molecular Mechanism of Targets Regulating Cell Autophagy

Abstract: <b><i>Background:</i></b> Autophagy is a lysosome-mediated catabolic process that maintains cell homeostasis and survival. It occurs not only in normal cells such as cardiac muscle cells, neurons, and pancreatic acinar cells but also in various benign and malignant tumors. The abnormal level of intracellular autophagy is closely related to multiple pathophysiological processes, including aging, neurodegeneration, infectious diseases, immune disorders, and cancer. Autophagy mainly plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…Numerous anticancer molecules have been found to induce autophagy (59). Studies have reported the inhibition or down regulation of both EZH2 and PRMT5, induce the apoptosis, autophagy, and cell cycle arrest (60)(61)(62). Autophagy exhibits a dual role in cancer, capable of both supporting cancer cell survival and inducing cell death (79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous anticancer molecules have been found to induce autophagy (59). Studies have reported the inhibition or down regulation of both EZH2 and PRMT5, induce the apoptosis, autophagy, and cell cycle arrest (60)(61)(62). Autophagy exhibits a dual role in cancer, capable of both supporting cancer cell survival and inducing cell death (79).…”
Section: Discussionmentioning
confidence: 99%
“…These marks are associated with cell cycle arrest (71, 78). This modification directly or indirectly involved in the regulation of different cell cycle regulators like cyclin D1, cdk4, cdk6, p21, and p27 in pancreatic cancer cells (72), and EGFR/cyclinD1 signaling in lung cancer (73), and WAF1/p21 in prostate cancer (60, 6971). These evidences substantiate our results that EA mediated reduced level of above histone modifications may be contributes to cell cycle arrest, (G0/G1, G2/S, G2/M) in MDA MB231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang Li [39] showed in his study that after the food restriction intervention, the mTOR activity was inhibited by the up-regulation of the corresponding cytoplasmic Ca2 + or the reduction of ATP synthesis, mAtg13 and ULK1 were dephosphorylated to form the mATg13-ULK1 complex, which eventually activated autophagy. Chen Zhijun [40] found that a period of exercise or food restriction intervention would increase the expression of autophagic proteins AMPK, PI3K, AKT in skeletal muscle and reduce the expression level of mTOR.…”
Section: Effect Of Different Intervention Methods On Akt and Mtor Mrn...mentioning
confidence: 99%
“…Autophagy was implicated in the progression of cancers of different origins, with it at higher levels closely correlating with lower overall survival. However, its roles in these malignancies are complicated, as it can work as either a promoter or suppressor of cell death depending on the stage and type of cancer [22][23][24]. By recycling the accumulated metabolites and positively regulating the metabolism of cancer cells, autophagy can function as a self-protective response against antitumor compounds, thus being a critical factor in the development of resistance to chemotherapy.…”
Section: Cellular Chloroquine Effectsmentioning
confidence: 99%